STRUCTURAL DESIGN AND FINITE ELEMENT ANALYSIS OF FOOD FORMING EQUIPMENT BASED ON 3D PRINTING TECHNOLOGY - ZHOU Jun; ZHANG LiFei; TAN LinFeng; HE ZeHui; ZHONG GaoYan (Jixie qiangdu)
Food 3D printing as a new technology has been widely used in recent years. Base on the forming characteristics of 3D printing of fluidized food, the design scheme of the equipment was constructed by using the modular design idea. The 3D model of the equipment was first established in PRO/E. Then, the model was imported into ANSYS Workbench to carry out the finite element Static analysis and modal analysis. Static analysis results show that the maximum stress is less than the allowable stress and the strength meet the requirements. After that the first six modes of the modal analysis of the equipment was extracted and the food 3D printing experiment platform was built on the basis of the simulation. Moreover, the dynamic characteristics experiment of the food printing equipment as well as the discharge experiment were carried out. By comparing the dynamic characteristics experiment results with the simulation results, the validity of the finite element analysis was verified and the accuracy of the discharge port is up to the corresponding standard, which indicates that the designed 3D printing equipment meets the requirements.